Mesenchymal stromal cells-based therapy in a murine model of elastase-induced emphysema: Simvastatin as a potential adjuvant in cellular homing. (October 2021) - Arruda de Faria, Carolina; Silva Júnior, Wilson Araújo; Caetano Andrade Coelho, Karoline Brito; Bassi, Mirian; Colombari, Eduardo; Zanette, Dalila Lucíola; Ribeiro-Paes, João Tadeu
Abstract: Chronic Obstructive Pulmonary Disease - COPD is characterized by the destruction of alveolar walls associated to a chronic inflammatory response of the airways. There is no clinical therapy for COPD. In this context, cell-based therapies represent a promising therapeutic approach for chronic lung disease. The goal of this work was to evaluate the effect of simvastatin on cell-based therapy in a mice emphysema model. Female FVB mice received intranasal instillation of elastase (three consecutive doses of 50 μL) in order to promote pulmonary emphysema. After 21 days of the first instillation, the animals were treated with Adipose-Derived Mesenchymal Stromal Cells (AD-MSC, 2.6 × 10 6 ) via retro-orbital infusion associated or not with simvastatin administrated daily via oral gavage (15 mg/kg/15d). Before and after these treatments, the histological and morphometrical analyses of the lung tissue, as so as lung function (whole body plethysmography) were evaluated. PAI-1 gene expression, an upregulated factor by ischemia that indicate a low survival of transplanted MSC, was also evaluated. The result regarding morphological and functional aspects of both lungs, presented no significant difference among the groups (AD-MSC or AD-MSC + Simvastatin). However, significant anatomical difference was observed in the right lung of the both groups of mice. The results shown a higher deposition of cells in the right lung, with might to be explained by anatomical differences (slightly higher right bronchi). Decreased levels of PAI-1 were observed in the simvastatin treated groups. The pulmonary ventilation was similar between the groups with only a tendency to a lower in the elastase treated animals due to a low respiratory frequency. In conclusion, the results suggest that both AD-MSC and simvastatin treatments could promote an improvement of morphological recovery of pulmonary emphysema, that it was more pronounced in the right lung. Highlights: Emphysema is a disabling progressive disease that has no cure. Cell therapy presents itself as a promising approach for emphysema. Evaluate the effect of simvastatin in a mice model of cell therapy for emphysema. Unrestrained whole body plethysmography to evaluate lung function in mice.